A Selective Review of Literature on Social Contribution of Libraries - Kamble, Ramkrushna Rajaram; Barad, Pradip Himmatrao (DESIDOC Journal of Library & Information Technology, 2021)
This article focused a selective review of literature on the role of libraries on educational; social & cultural; economical and political development under the title ‘A selective Review of Literature on Social Contribution of Libraries’. Libraries are changing their nature in the modern age and they offer their services to the user from various requirements of them and play a very important role in society. The library is considered as the heart of an educational institution as well as plays a role as the backbone of an educational institution. And also by offering various services, these libraries added value to education, social & cultural, economic, and political development. In this paper, the literature published on the social contribution of libraries is studied, analysed and, explained. The social contribution of libraries is crucial in the educational, social & cultural, economic and, political development of the nation. From this article scholars and researchers can understand how libraries play the important role in society and also aware of the literature available in this area.